Exploring the antecedents of dynamic capabilities in a software product company : Dynamic capabilities enabling adaptation to change - Herrala, Hannes (My University, 2022)
Firms operating in the software industry are constantly faced with new opportunities and threats that stem from the volatility of the market. Customer needs change and competing solutions come up in high frequency as software development practices have gotten better during the last decade. Companies need to obtain dynamic capabilities to address rapidly changing markets. This study examines how dynamic capabilities and their underlying microfoundations enable adaption to change in the environment. The study was conducted as a qualitative case study of Company X. Data was gathered using semi-structured interviews with employees in the area of product management. Furthermore, data from interviews were complemented with various documentation to understand the phenomenon better. The findings of this study show that sensing, seizing, and transforming dynamic capabilities deploy their underpinning microfoundations in ways that enable the company to sense opportunities and threats, address those findings, and transform its (intangible) resource base as required for handling change in the environment. The phenomenon results in three distinct outcomes that are represented as principles of agility: agility foundations, agility fostering culture and learning fast. This thesis contributes to the literature on dynamic capabilities, product management and agility. The dynamic capabilities literature has previously overlooked the software industry, and this study fills this gap

Ohjelmistoalalla toimivat yritykset kohtaavat jatkuvasti uusia mahdollisuuksia ja uhkia, jotka syntyvät markkinoiden epävakaudesta. Asiakastarpeet muuttuvat ja kilpailevia ratkaisuja syntyy paljon, sillä ohjelmistokehityskäytännöt ovat parantuneet viime vuosikymmenen ajan. Yrityksillä on oltava dynaamisia kyvykkyyksiä, jotta ne voivat vastata nopeasti muuttuviin markkinoihin. Tässä tutkimuksessa tarkastellaan, miten dynaamiset kyvykkyydet ja niiden taustalla olevat mikroperustat mahdollistavat sopeutumisen ympäristön muutoksiin. Tutkimus toteutettiin laadullisena tapaustutkimuksena (Company X). Tiedot kerättiin puolistrukturoiduilla haastatteluilla, joita tehtiin tuotehallinnan työntekijöiden kanssa. Lisäksi haastatteluista saatuja tietoja täydennettiin erilaisilla asiakirjoilla, jotta tutkittava ilmiö ymmärrettäisiin paremmin. Tutkimuksen tulokset osoittavat, että kolme dynaamista kyvykkyyttä havaitseminen (sensing), hallitseminen (seizing) ja muuntaminen (transforming), käyttävät perustana olevia mikroperustojaan tavoilla, joiden avulla yritys pystyy havaitsemaan mahdollisuuksia ja uhkia, puuttumaan näihin havaintoihin ja muuntamaan (aineetonta) resurssiperustaansa ympäristön muutosten hallinnan edellyttämällä tavalla. Ilmiö johtaa kolmeen eri lopputulokseen, jotka esitetään ketteryyden periaatteina: ketteryyden perusteet, ketteryyttä edistävä kulttuuri ja nopea oppiminen. Tämä tutkielma täydentää dynaamisia kyvykkyyksiä, tuotehallintaa ja ketteryyttä käsittelevää kirjallisuutta. Dynaamisten kyvykkyyksien kirjallisuudessa on aiemmin jätetty huomiotta ohjelmistoala, ja tämä tutkimus täyttää tämän aukon.
Keywords: Dynamic capabilities, microfoundations, product management, product development, agility, software